Chlorination of Substituted Aromatics on Graphite Anode - Krishnamoorthy, T.K. (Asian Journal of Chemistry, 2010)
Electro-chlorination on selected aromatic compounds has been carried out on graphite anode in 1:1 water-ethanol solutions. The major anodic products are found to be chloro substituted aromatic compounds. The most probable mechanism for this anodic transformation has been proposed and substantiated by quantitative studies.